Rola marketingu w budowaniu przewagi konkurencyjnej regionu turystycznego w Unii Europejskiej - Rudolf, Wawrzyniec (The Role of Marketing in Developing Competitive Advantage of a Tourist Region in The European Union, 2005)
Polish accession into European Union has increased the competitiveness between the regions. In the article the current economic situation of Polish regions (voivodships) has been critically analysed. They are lagging behind, especially when we compare their regional GDP per capita with similar indicators from the regions of the old member states. How to change the situation - how to increase the comparative position of Polish regions? is the key question of the article. The author has classified factors of region's competitiveness. The instrumental factors, one of the categories, has been pointed out. The way of region's management belongs to that group of factors. The author claims that it is the marketing concept in regions' management as the best response to increased competition between regions. The author formulates possible marketing strategies to be implemented at the level of regional authorities and recommends the strategies targeted at attracting capital and tourists from outside. These are the Structural Funds which can substantially co-finance the projects prepared by local self - governments, institutions, and enterprises, which have the impact for the tourist functions of the regions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 56-72